ПОТОК ИНОСТРАННЫХ ЭЛЕКТРОННЫХ ЖУРНАЛОВ: КАЧЕСТВЕННЫЕ И КОЛИЧЕСТВЕННЫЕ ХАРАКТЕРИСТИКИ (Библиосфера, 2010)
With the advent of scientific electronic journal at the end of XX century the information flow accumulated in this channel of scientific communication and available for specialists and researches of SB RAS has increased many times in comparison with the information flow in printed journals. An attempt is made to determine qualitative and quantitative characteristics of foreign electronic journals, accessible for the specialists of SB RAS.